Correlation between anthropometric and biological parameters of the offspring and parental plasma 25-hydroxyvitamin D levels: a cross-sectional study conducted at Oran, Algeria - Sara Mama Abadi; Habib Hammou; Lidia Saidi; Soumia Fenni; Tawfik Addi; Ilyes Meguenni; Seyf El Islem Negadi; Sahra Meziane; Farid Boubred; Jean-François Landrier (BMC Pregnancy and Childbirth)
Abstract Background Vitamin D is critical in overall health, particularly during pregnancy, as it supports a healthy pregnancy and promotes proper fetal development. This study examined the link between parental 25-hydroxyvitamin D (25(OH)D) deficiency and their offspring’s anthropometric and biological parameters. Methods A cross-sectional study was conducted involving 50 Algerian families, which included 50 pregnant women in their third trimester, 50 fathers, and 50 newborns. Blood samples were collected from both parents and the umbilical cord of the newborns. Serum 25(OH)D concentrations were measured, and demographic and health-related information was gathered from the participants. The anthropometric parameters of the newborns were recorded at birth. Results In our study, 16% of women were insufficient in 25(OH)D, 54% were deficient, and the remaining 30% exhibited severe deficiency, with mean 25(OH)D levels of 24.53 ng/ml, 14.23 ng/ml, and 7.69 ng/ml, respectively. Among males, 40% were insufficient, 42% were deficient, and 18% had severe deficiency, with mean 25(OH)D levels of 25 ng/ml, 15.78 ng/ml, and 8.53 ng/ml, respectively. Furthermore, 24% of newborns were insufficient, 52% were deficient, and 24% had severe deficiency, with mean 25(OH)D levels of 23.53 ng/ml, 13.46 ng/ml, and 7.53 ng/ml, respectively. Maternal 25(OH)D levels were positively correlated with the anthropometric parameters of newborns (height, femur length, weight, and Apgar scores at 1 and 5 min after birth). Conversely, paternal deficiency showed no correlation with these parameters. Conclusion 25(OH)D deficiency significantly impacts newborns and represents a significant risk to their development, whereas paternal deficiency has no impact on the measured anthropometric parameters of newborns.